Procurement activity of consumer cooperation in the Krasnodar Territory in the conditions of economic recovery (1943–1945) - A. E. Mesropyan (Гуманитарные и юридические исследования)
Introduction. The relevance of the problem considered in the article is connected with the need for creative use of the experience of economic activity of consumer cooperation.   The novelty of the research is connected with the study of the problem that has not received proper coverage in the historical literature.   The purpose of the study is to analyze the procurement activities of consumer cooperatives of the Krasnodar Territory during the Great Patriotic War.   Materials and methods. The research is based on the principles of objectivity, historicism and a systematic approach. The following special historical methods were used in the preparation of the study: historical-genetic, historical-comparative and statistical.   Analysis. During the Great Patriotic War, the importance of procurement activities of consumer cooperatives has significantly increased. In particular, the procurement of agricultural products and raw materials played an important role in the conditions of the restoration of the economy of the Krasnodar Territory in 1943–1945. Despite the objective difficulties, the Kuban consumer cooperation has been increasing the volume of agricultural products and raw materials every month. Metal billets were of primary importance as it was one of the areas of assistance to the front. The main factors in the development of procurement work were the increase in the level of procurement organization by the leadership of the district consumer unions and the procurement office, as well as the hard work of employees. At the same time, during the procurement, such shortcomings as the limited availability of goods allocated for exchange, the lack of the necessary amount of containers, the irresponsible attitude of a number of leaders of consumer societies and theft of material values were revealed. At the end of the war, certain successes were achieved in the fight against these negative phenomena.   Results. According to the results of the study, it can be concluded that the procurement activity of consumer cooperatives played an important role in the conditions of economic recovery of the Krasnodar Territory.